Analysis of the Need for Digital Teaching Materials in Indonesian Language Learning in Elementary Schools - Dine Trio Ratnasari; Yeni Sulaeman; Jumanah Jumanah (STAI Hubbulwathan Duri, 2025)
The integration of digital technologies in education has become increasingly essential, particularly in supporting interactive and student-centered learning. This study aims to analyze the needs of primary school teachers regarding the use of digital teaching materials in Indonesian language instruction. A qualitative descriptive approach was employed involving 24 classroom teachers from 10 primary schools in Lebak Regency, Indonesia, selected through simple random sampling. Data were collected using structured interviews and analyzed thematically to identify recurring patterns and themes. The findings indicate that most teachers still rely on conventional teaching materials such as textbooks, visual aids, and simple instructional media. Teachers expressed a strong need for digital teaching materials, particularly those utilizing Augmented Reality (AR) to support topics such as essay writing, speed reading, and grammar structures. These materials are expected to enhance student engagement, simplify abstract content, and promote 21st-century learning competencies. The study provides practical recommendations for stakeholders and curriculum developers to create accessible and interactive digital resources tailored to teachers’ needs in the digital era.